2013
DOI: 10.1190/geo2012-0338.1
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic 3D full-waveform inversion

Abstract: We have developed and implemented a robust and practical scheme for anisotropic 3D acoustic full-waveform inversion (FWI). We demonstrate this scheme on a field data set, applying it to a 4C ocean-bottom survey over the Tommeliten Alpha field in the North Sea. This shallow-water data set provides good azimuthal coverage to offsets of 7 km, with reduced coverage to a maximum offset of about 11 km. The reservoir lies at the crest of a high-velocity antiformal chalk section, overlain by about 3000 m of clastics w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
238
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 402 publications
(238 citation statements)
references
References 37 publications
0
238
0
Order By: Relevance
“…Initial applications of FWI were performed in the time domain, but were limited given the high computational demand of the method (Kolb et al 1986). Three decades later and FWI is still performed based on these underlying principles, with modern codes capable of performing FWI in either the time or frequency domain, in two or three dimensions, approximating either the acoustic or elastic wave equation, and can include the effects of seismic attenuation and anisotropy (e.g., Pratt 1999; Brossier et al 2009;Warner et al 2013). It has also been shown that the maximum achievable resolution using these codes is on the order of half the seismic wavelength, making it superior to travel-time tomography .…”
Section: Full Waveform Inversionmentioning
confidence: 99%
See 2 more Smart Citations
“…Initial applications of FWI were performed in the time domain, but were limited given the high computational demand of the method (Kolb et al 1986). Three decades later and FWI is still performed based on these underlying principles, with modern codes capable of performing FWI in either the time or frequency domain, in two or three dimensions, approximating either the acoustic or elastic wave equation, and can include the effects of seismic attenuation and anisotropy (e.g., Pratt 1999; Brossier et al 2009;Warner et al 2013). It has also been shown that the maximum achievable resolution using these codes is on the order of half the seismic wavelength, making it superior to travel-time tomography .…”
Section: Full Waveform Inversionmentioning
confidence: 99%
“…In this study we perform a 2D time-domain, acoustic, isotropic FWI, using the codes of Warner et al (2013). In this code, synthetic traces are calculated through a starting model using a finite difference method and are subsequently scaled so that their RMS amplitude matches that of their corresponding observed trace.…”
Section: Full Waveform Inversionmentioning
confidence: 99%
See 1 more Smart Citation
“…-Composite shot lists: This last strategy [27,49] simply distributes the complete shot list in a subset of shots which are run sequentially at each gradient iteration. In this way, for a fixed number of gradient iterations, the total amount of shots simulated is smaller, reducing the computational resources needed.…”
Section: Workflow Optimization Overviewmentioning
confidence: 99%
“…Over the past three decades, most FWI techniques have been designed to recover only a P-wave velocity model because of the high computational cost (e.g., Gauthier et al, 1986;Pratt, 1999). The recent progress in high-performance computing and the improvement in data acquisition resulted in the extension of FWI to 2D and 3D acoustic and elastic transverse isotropic media with a vertical axis of symmetry (VTI) (e.g., Warner et al, 2013;Operto et al, 2014;Wu and Alkhalifah, 2016;Kamath et al, 2017). This extension has resulted in challenges related to the trade-offs between the model parameters in our inversion process.…”
Section: Introductionmentioning
confidence: 99%